MEASURING SPOKEN VOCABULARY LOAD ON MEDICAL ENGLISH STUDENTS: A LEARNER CORPUS EVALUATION - Muhammad Rudy; Diah Kristina; Sri Samiati Tarjana (Informascope, 2019)
English for Specific Purposes (ESP) teaching urges the students to have a deep understanding of specific vocabularies. Specifically, in medical English class, spoken diagnosis explanation involves specific vocabularies. This corpus study was aimed to reflect the students' achievement of spoken vocabulary during speaking practice on explaining the diagnosis. Computer software was utilized to calculate frequency and range of words. The students' vocabularies were compared with listening tapescript corpora from a medical English textbook to evaluate vocabulary pattern. Additionally, the students' spoken corpora were contrasted with 2000 high-frequency words and other three word lists to assess word distribution. This study revealed that medical students used few specialized vocabularies in order to deliver their explicable message to the patient. The analysis of students' vocabulary can be used as a reference to contemplate the success of language instruction and future betterment, particularly spoken diagnosis explanation at medical English program.